SURGICAL TERMS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS - Nodira Uskenbayeva,; Dilorom Mirsagatova, (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This article explores surgical terminology in English and Uzbek, highlighting linguistic similarities, differences, and translation challenges. Drawing from medical dictionaries and scholarly works, it compiles a bilingual glossary focused on surgical procedures, instruments, and related concepts. The study underscores the importance of accurate translation for healthcare communication in multilingual contexts like Uzbekistan. Key findings reveal heavy reliance on borrowing from Latin/Greek roots in both languages, with Uzbek incorporating Turkic and Russian influences. Challenges include semantic shifts and cultural adaptations. The discussion addresses implications for medical education and practice.